Business Strategy of PT Soca Cipta Niaga - Risnandar, Mohammad Tedi; Larso, Dwi (The Indonesian Journal of Business Administration, 2013)
Growth of Muslim population in Indonesia goes rapidly every year, not only in Indonesia but also worldwide. The need for special Muslim socks is very high mainly to support the hajj and umroh which are performed annually. PT Soka Cipta Niaga (PT SCN), one of the manufacturers of Muslim socks, is currently emergig.